The complete chloroplast genome of Tilia endochrysea Handel-Mazzetti 1926 (Malvaceae). Issue 3 (4th March 2022) - Wang, Huanli; Huang, Xi; Yan, Lingjun; Tang, Shijie
Abstract: Tilia endochrysea Handel-Mazzetti 1926, distributed in the southern margin of Chinese Subtropical Zone, is the only one species in genus Tilia has dehiscent fruit. The whole chloroplast genome of T. endochrysea was 162, 838 bp with 36.46% GC content, including a large single-copy (LSC) region of 91, 264 bp, a small single-copy (SSC) region of 20, 414 bp, and a pair of inverted repeats (IRs) of 51, 160 bp. The chloroplast genome encodes 130 genes, including 85 protein-coding genes, 37 tRNA genes, and eight rRNA genes. The phylogenetic tree shows T. endochrysea was the basal taxon in Tilia and closely related to Craigia yunnanensis (Smith et Evans 1921).